Cerita Anak Di Dalam Al-Qur’an: (Kajian Intertekstualitas Julia Kristeva) - Kholifah, Latif Nur (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
This article focused on the importance of a story as an appropriate method to communicate the theory in the Qur’an which is commited not only by reciting or read the verses of Qur’an to children but through the story which has been added and expanded that does not relieve the value that contained in the Qur’an so it easily can be understood by the children. This can be seen by Julia Kristeva’s theory Intertextuality which said that every creation has a relation with the previous creation, as well with some stories that spreads in community as the form of expansion of the verses in Al-Qur’an which contains the previous story that has been expanded to make it more interesting and not contradicting with the Qur’an.